Methane potential of oat husk waste streams in anaerobic digestion - Tuominen, Sonja (My University, 2024)
The production of oat grains creates side streams of oat husks that are mainly unsuitable for human consumption. Globally it reaches around 1500 million tons of agricultural waste from cereal production only. CH-Bioforce’s process utilizes oat husk powder to extract polymers, producing hemicellulose permeate as a waste stream. In this study, methane is produced by anaerobic digestion using industrial inoculum and oat husk powder to determine oat husk powders methane potential. Oat husk powder and hemicellulose permeate are analysed for their chemical composition to estimate digestion properties and potential as a biobased material. Methane production digestion setup included inoculum control, microcrystalline cellulose control and sample, with three replicate samples of each. Digestion is located in a shaker incubator (35 °C, 200 rpm, 30 days). Biogas produced in the digestion is lead to sodium hydroxide (5 M) to capture carbon dioxide, after which methane is collected. Detected production of digestion control was approximately 300 ml of methane, and in double digestion methane production of digestion control was 210 ml of methane and oat husk powder sample by 100 ml of methane in 30 days. Other digestions did not indicate any biomethane produced. Compared to maximum potential of 1930 ml digestions did not exceed predicted methane production. These are not scientifically viable results, because only one control and one sample showed results between two digestions. Oat husk powder is considered as a potential methane production substrate according to the chemical composition and literature references. Hemicellulose permeate was not considered as a possible methane production substrate due to high sodium concentrations.
Keywords: anaerobic digestion, methane potential, agricultural waste stream, oat husk